Legal Protection of Mahakam Dolphins Through Water Conservation Areas in Kutai Kartanegara Regency - Rosmini Rosmini; Zainuddin Zainuddin; Syifa Nur Aini (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
Mahakam dolphins are aquatic mammals (not fish) that live in freshwater rivers in the tropics and live in groups. The Mahakam dolphins, as endemic to the Mahakam River, is already threatened with extinction and needs protection to prevent the extinction from occurring. This paper explores the problems, namely the legal protection of the Mahakam Dolphin in Kutai Kertanegara Regency and the determination of conservation of the Mahakam Dolphin habitat area in Kutai Kertanegara Regency. The research method used is normative legal research (doctrinal) with the collection of legal materials. The results showed that the government of Kutai Kartanegara Regency has tried to protect the Mahakam dolphin through the establishment of the Mahakam Dolphins Habitat Water Conservation Area. This stipulation serves as an instrument in providing guidelines for the Regional Government and stakeholders in Kutai Kartanegara Regency in the context of organizing activities for the protection and preservation of the Mahakam dolphins.